Mucosal Immunization with an Influenza Vector Carrying SARS-CoV-2 N Protein Protects Naïve Mice and Prevents Disease Enhancement in Seropositive Th2-Prone Mice - Mariia V. Sergeeva; Kirill Vasilev; Ekaterina Romanovskaya-Romanko; Nikita Yolshin; Anastasia Pulkina; Daria Shamakova; Anna-Polina Shurygina; Arman Muzhikyan; Dmitry Lioznov; Marina Stukova (Vaccines)
Background/Objectives: Intranasal vaccination enhances protection against respiratory viruses by providing stimuli to the immune system at the primary site of infection, promoting a balanced and effective response. Influenza vectors with truncated NS1 are a promising vaccine approach that ensures a pronounced local CD8+ T-cellular immune response. Here, we describe the protective and immunomodulating properties of an influenza vector FluVec-N carrying the C-terminal fragment of the SARS-CoV-2 nucleoprotein within a truncated NS1 open reading frame. Methods: We generated several FluVec-N recombinant vectors by reverse genetics and confirmed the vector’s genetic stability, antigen expression in vitro, attenuation, and immunogenicity in a mouse model. We tested the protective potential of FluVec-N intranasal immunization in naïve mice and seropositive Th2-prone mice, primed with aluminium-adjuvanted inactivated SARS-CoV-2. Immune response in immunized and challenged mice was analyzed through serological methods and flow cytometry. Results: Double intranasal immunization of naïve mice with FluVec-N reduced weight loss and viral load in the lungs following infection with the SARS-CoV-2 beta variant. Mice primed with alum-adjuvanted inactivated coronavirus experienced substantial early weight loss and eosinophilia in the lungs during infection, demonstrating signs of enhanced disease. A single intranasal boost immunization with FluVec-N prevented the disease enhancement in primed mice by modulating the local immune response. Protection was associated with the formation of specific IgA and the early activation of virus-specific effector and resident CD8+ lymphocytes in mouse lungs. Conclusions: Our study supports the potential of immunization with influenza vector vaccines to prevent respiratory diseases and associated immunopathology.